Anthranilate Synthetase, an Enzyme Specified by the Tryptophan Operon of Escherichia coli: Purification and Characterization of Component I - Ito, Junetsu (1969)
A procedure employed in the purification of anthranilate synthetase component I of Escherichia coli is described. The purified component appears homogeneous by starch gel electrophoresis and by sedimentation analysis. A molecular weight of 60,000 was estimated by gel filtration of Sephadex G-100. This value is consistent with the molecular weight estimated from the sedimentation and diffusion coefficients. Purified anthranilate synthetase component I cannot use glutamine as substrate and thus has no activity in the reaction of chorismate + l-glutamine → anthranilate; however, it is active when ammonium sulfate is provided as amino donor. Sucrose density gradient analyses showed that ammonium sulfate does not affect the sedimentation velocity of component I. The ultraviolet absorption and fluorescence spectra of the purified component indicated that it contains tryptophan. Peptide pattern and extract complementation evidence suggested that the protein is a single polypeptide chain. Enzyme activity measurements indicated that wild-type E. coli produces equimolar amounts of at least four of the five polypeptides specified by the operon. Purified anthranilate synthetase component I is inhibited by l-tryptophan.